Cerebello-basal ganglia connectivity fingerprints related to motor/cognitive performance in Parkinson's disease. (November 2020) - Kawabata, Kazuya; Watanabe, Hirohisa; Bagarinao, Epifanio; Ohdake, Reiko; Hara, Kazuhiro; Ogura, Aya; Masuda, Michihito; Kato, Toshiyasu; Tsuboi, Takashi; Maesawa, Satoshi; Katsuno, Masahisa; Sobue, Gen
Abstract: Introduction: The role of the cerebellum in Parkinson's disease (PD) has attracted increasing attention; however, the role of functional connectivity (FC) between the basal ganglia and particular cerebellar subregions remains to be elucidated. We aimed to clarify the FC and its contribution to motor and cognitive performances in patients with PD. Methods: We included 99 patients with PD and 99 age- and sex-matched healthy controls in this study. We created a cerebellar functional parcellation by performing cerebellum-only independent component analysis. Using the functional parcellation map, we performed seed-based connectivity analysis using each region as a seed and extracted the mean correlation coefficients within the thalamus and basal ganglia, including the caudate, pallidum, putamen and subthalamic nucleus. We examined the group differences and correlations with the motor and general cognitive scores. In addition, we conducted a mediation analysis to clarify the relationship among FC, motor severity, and cognition. Results: The PD group showed decreased FC between a wide range of cerebellar subregions and the basal ganglia. Motor severity was correlated with FC between the subthalamic nucleus and posterior Crus I/II, and general cognitive performance scores correlated with FC between the caudate nucleus and medial-posterior part of the Crus I/II (p < 0.05, corrected for multiple comparisons). The cerebello-caudate network had a direct effect on cognitive performance (p = 9.0 × 10 −3 ), although partially mediated by motor performance (p = 8.2 × 10 −3 ). Conclusion: FC between cerebellar Crus I/II and divergent basal ganglia related to motor and cognitive performance in PD. Highlights: We generated a functional cerebellar parcellation map using cerebellum-only ICA. Cerebellar lobules and basal ganglia networks were decreased in PD. Connection between Crus I/II and the STN was associated with motor severity. Connection between Crus I/II and the caudate was related to cognitive performance.